Concurrent training and detraining: brief review on the effect of exercise intensities - Sousa, António C. (2020)
Concurrent resistance and aerobic training (CT) has been applied to optimize both strength and aerobic performance. However, it should be carefully prescribed, as there are some factors, as the training intensity, which have strong influence on training adaptations. Thus, we conducted a systematic review to analyze the scientific evidence regarding aerobic and resistance exercise intensities during CT and their effect on performance outcomes. The effects of exercise intensity on a subsequent detraining period were also assessed. Nine studies met the inclusion criteria, the risk of bias was assessed, and the percentage of changes and effect sizes were quantified. CT improved running times (10 m, 30 m and 10 km) and strength performance (one-repetition maximum, countermovement jump) regardless of exercise intensity used (4-47%, ES=0.4-2.8). Nevertheless, higher aerobic training intensities (≥ lactate threshold intensity) resulted in higher aerobic gains (5-10%, ES=0.3-0.6), and greater neuromuscular adaptations were found when higher resistance loads (≥ 70% of maximal strength) were used (10-14%, ES=0.4-1.3). Most training-induced gains were reversed after 2-4 weeks of detraining. Although further research is needed, it seems that higher intensities of aerobic or resistance training induce greater aerobic or neuromuscular gains, respectively. Nevertheless, it seems that higher resistance training loads should be combined with lower aerobic training intensities for increased strength gains and minimal losses after detraining.